2018
DOI: 10.1111/cogs.12691
|View full text |Cite
|
Sign up to set email alerts
|

Visual Statistical Learning With Stimuli Presented Sequentially Across Space and Time in Deaf and Hearing Adults

Abstract: This study investigated visual statistical learning (VSL) in 24 deaf signers and 24 hearing non-signers. Previous research with hearing individuals suggests that SL mechanisms support literacy. Our first goal was to assess if VSL was associated with reading ability in deaf individuals, and if this relation was sustained by a link between VSL and sign language skill. Our second goal was to test the Auditory Scaffolding Hypothesis, which makes the prediction that deaf people should be impaired in sequential proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…Our null hypothesis is confirmed by the results, offering no support to the Auditory Scaffolding Hypothesis [18]. Rather, our results are consistent with the growing body of literature finding no implicit learning deficit in deaf children, thus suggesting that implicit learning is not impaired by a lack of auditory stimulation [23][24][25][26][27]. Given that children with cochlear implants scored significantly behind the typically hearing children in the verbal tasks that involved explicit processing and knowledge (verbal rehearsal and verbal elaboration as measured by the digit span task, and language skills by the formulated sentences task), our results suggest that implicit learning is independent of explicit learning and not significantly affected by poor auditory input.…”
Section: Plos Onesupporting
confidence: 63%
See 3 more Smart Citations
“…Our null hypothesis is confirmed by the results, offering no support to the Auditory Scaffolding Hypothesis [18]. Rather, our results are consistent with the growing body of literature finding no implicit learning deficit in deaf children, thus suggesting that implicit learning is not impaired by a lack of auditory stimulation [23][24][25][26][27]. Given that children with cochlear implants scored significantly behind the typically hearing children in the verbal tasks that involved explicit processing and knowledge (verbal rehearsal and verbal elaboration as measured by the digit span task, and language skills by the formulated sentences task), our results suggest that implicit learning is independent of explicit learning and not significantly affected by poor auditory input.…”
Section: Plos Onesupporting
confidence: 63%
“…Studies have suggested that the linguistic variability shown by deaf children might result from a deficit in their implicit learning skills [18,20,21]. However, several studies have presented data that challenge this hypothesis [23][24][25][26][27], thereby creating a vibrant theoretical and methodological debate in this area of research. The main aim of the present study was to investigate the dynamic implicit learning of temporal regularities in cochlear-implanted deaf children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This focus has often been underpinned by a theoretical perspective in which early exposure to sound is seen as vital for the typical development of cognitive abilities that relate to the representation and processing of sequential information, which in turn is associated with language development (Conway et al, 2009, 2011a,b; Pisoni et al, 2016). Although there have been several failures to replicate critical empirical findings cited in support of the theory (e.g., Giustolisi and Emmorey, 2018; Hall et al, 2018; von Koss Torkildsen et al, 2018), evidence for a link between cognitive ability and language outcomes remains.…”
Section: Introductionmentioning
confidence: 99%